Helping learners think more hopefully about life after school: the usefulness of participatory visual strategies to make career education more contextually relevant - Smit, Suegnet; Wood, Lesley; Neethling, Marinda (Faculty of Education, University of the Free State, 2015)
Learners living in challenging socio-economic circumstances face limited opportunities for further education and employment. In this context, formal career guidance which merely provides information about specific jobs and how to access them may be of little use. This article explores the usefulness of participatory visual strategies as a pedagogical tool for teachers to help learners think more critically, realistically and hopefully about their future life opportunities. Analysed through a resilience lens, findings indicated that the strategies inspired hope in learners; helped them identify assets and barriers in their social ecologies; develop a sense of agency and responsibility for deciding on their futures; and care more for other people, all of which will help them make more constructive choices for life after school. The findings might help teachers make their career education more relevant for children who live in contexts of adversity.
Keywords: Career guidance; Life Orientation; Mind maps; Photo voice; Resilience theory; Socio-economic challenges